Implementing Islamic School Culture Policy to Strengthen ‎Teacher Professionalism: A Multi-Case Study in North Aceh, ‎Indonesia - Zulkarnen; Amiruddin Siahaan; Abd. Mukti (Yayasan Darussalam Bengkulu, 2026)
Islamic school culture policy has become a strategic issue in Aceh’s education system because schools are expected to integrate Islamic values, local cultural identity, teacher professionalism, and educational quality improvement into daily institutional practices. This study aims to analyze the formulation, implementation, and evaluation of Islamic school culture policy in strengthening teacher professionalism in North Aceh, Indonesia. A qualitative approach with a multi-case study design was employed at SMA Negeri 1 Lhoksukon and MAS Al Muslimun Lhoksukon. Data were collected through in-depth interviews, observation, and document analysis, and were analyzed using within-case and cross-case analysis to identify institutional patterns, similarities, and differences between the two schools. The findings show that both schools formulate Islamic school culture policy through value-based and contextual processes grounded in Islamic values, Aceh educational regulations, school vision, institutional rules, and stakeholder participation. Policy implementation is reflected in religious habituation, Qur’anic programs, Islamic discipline, teacher role modelling, community involvement, and the development of an Islamic professional work culture. However, the two schools differ in governance patterns: SMA Negeri 1 Lhoksukon is characterized by principal-driven leadership and program-based innovation, whereas MAS Al Muslimun Lhoksukon is more strongly guided by foundation statutes, institutional rules, and boarding-based Islamic culture. Policy evaluation is conducted through internal monitoring and external accountability, although both schools still require more measurable indicators to assess the direct contribution of Islamic school culture to teacher professional performance. This study implies that Islamic school culture policy should not be limited to symbolic religious activities, but should be designed as an integrated organizational mechanism that strengthens teacher professionalism, school leadership, institutional identity, and sustainable quality improvement in Islamic-oriented educational institutions.